2021
DOI: 10.1093/cid/ciab474
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epidemiologic Analyses of an Outbreak of Pneumocystis jirovecii Pneumonia Among Kidney Transplant Recipients in the United States

Abstract: Background Pneumocystis jiroveciii is an opportunistic fungus that causes Pneumocystis pneumonia (PCP) in immunocompromised hosts. Over an 11-month period, we observed a rise in cases of PCP among kidney-transplant recipients (KTR), prompting an outbreak investigation. Methods Clinical and epidemiologic data were collected for KTR diagnosed with PCP between July 2019 and May 2020. Pneumocystis strain typing was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…It is noteworthy to disclose a cluster of PJP infections have occurred within our transplant center, which adds to the available evidence of inter-human PJP transmission that may occur within transplant centers. [8][9][10] It is important to consider the inherent risk of infection transmission, such as PJP, with repeated exposure to healthcare facilities that are required for BELA infusions.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to disclose a cluster of PJP infections have occurred within our transplant center, which adds to the available evidence of inter-human PJP transmission that may occur within transplant centers. [8][9][10] It is important to consider the inherent risk of infection transmission, such as PJP, with repeated exposure to healthcare facilities that are required for BELA infusions.…”
Section: Discussionmentioning
confidence: 99%
“…The additional 73 studies were evaluated furtherly through a full‐text review. Ultimately, a total of 27 retrospective studies published between 1995 and 2022 were included in the meta‐analysis 6,8,14–38 . Among them, 15 studies are from Europe, 6 are from Asia, 5 are from the Americas, and 1 is from Oceania.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, it was found that eight factors are associated with PJP occurrence: age at transplantation, ABO‐incompatibility, acute rejection, CMV infection, BK viremia, anti‐PJP prophylaxis, eGFR and lymphocyte count. Some studies have investigated risk factors for PJP before, such as age, CMV infection, transplant rejection episodes, dialysis time and Tacrolimus dose 7,9,14–38 . However, these conclusions differ, which could be attributed to the fact that people are from different regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…However, single-strand cultures were not the goal of this study—our aim was simply to establish a stable culture at all. A single patient often harbors more than one strain of P. jirovecii at the same time [ 6 , 66 , 67 , 68 ], so the idea of a “single-strain” culture is specious anyway. Therefore, we used mixed P. jirovecii strains from 3 to 4 BALF samples, which stabilized the system and ensured growth in this first attempt, which resulted in 41 successful flask cultures.…”
Section: Discussionmentioning
confidence: 99%